1998
DOI: 10.1007/s002130050496
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the extinction/reinstatement model of drug craving

Abstract: The effects of chronic desmethylimipramine (DMI) treatment on measures of incentive motivation for cocaine were assessed in order to investigate the predictive validity of the extinction/reinstatement model of drug craving. Rats were trained to respond for cocaine infusions (0.75 mg/kg per 0.1 ml i.v.) or received yoked-saline infusions during daily 3-h sessions. A light and tone were presented with the infusions. Following self-administration training, each group received daily injections of either saline or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 34 publications
4
83
0
1
Order By: Relevance
“…Consistent with a role of conditioning factors in the resumption of drug abuse habits, several studies in animals have demonstrated that drug-associated stimuli can elicit a transient recovery of extinguished responding at a lever previously associated with cocaine selfadministration (e.g., deWit and Stewart 1981; Fuchs et al 1998). However, little information is available, to date, about the persistence of cue-induced drug-seeking behavior.…”
Section: The Conditioning Of Cocaine's Pharmacological Actions With Ementioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with a role of conditioning factors in the resumption of drug abuse habits, several studies in animals have demonstrated that drug-associated stimuli can elicit a transient recovery of extinguished responding at a lever previously associated with cocaine selfadministration (e.g., deWit and Stewart 1981; Fuchs et al 1998). However, little information is available, to date, about the persistence of cue-induced drug-seeking behavior.…”
Section: The Conditioning Of Cocaine's Pharmacological Actions With Ementioning
confidence: 92%
“…A wealth of clinical studies point towards drug-related stimuli or events as a critical factor in the long-lasting compulsion to abuse drugs. This literature suggests that environmental stimuli repeatedly paired with the subjective actions of cocaine throughout an individual's history of drug abuse can produce intense drug craving (Childress et al 1988;Ehrman et al 1992;Kilgus and Pumariega 1994;Robbins et al 1997;Satel et al 1995;Wallace 1989) or elicit automatic behavioral responses (Miller and Gold 1994;Tiffany and Carter 1998) that may lead to relapse.Consistent with a role of conditioning factors in the resumption of drug abuse habits, several studies in animals have demonstrated that drug-associated stimuli can elicit a transient recovery of extinguished responding at a lever previously associated with cocaine selfadministration (e.g., deWit and Stewart 1981;Fuchs et al 1998). However, little information is available, to date, about the persistence of cue-induced drug-seeking behavior.…”
mentioning
confidence: 92%
“…Further evidence supporting the construct validity of the model are that neuroimaging studies in human addicts and examination of immediate early gene (IEG) expression in animals that reveal the same brain regions are activated by cocaine-paired cues (Childress et al, 1999;Garavan et al, 2000;Grant et al, 1996;Kufahl et al, 2009;Wang et al, 1999;Zavala et al, 2008). In addition, compounds found to decrease self-reports of craving in humans have been shown to attenuate cue-elicited drug-seeking behavior in animals (Fuchs et al, 1998;Yahyavi-FirouzAbadi and See, 2009), demonstrating predictive validity and overall utility of the cue reinstatement model. Fos protein expression is an established method for identifying brain circuits associated with cocaine-induced conditioning effects (Brown et al, 1992;Crawford et al, 1995;Neisewander et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Such drug-associated stimuli evoke memories of the effects of the drug, induce craving in abstinent addicts, and precipitate relapse to a drug-taking habit (Gawin and Kleber, 1986;O'Brien et al, 1998;Childress et al, 1999). In experimental animals, a conditioned stimulus (CS) paired repeatedly with the self-administration of cocaine similarly induces relapse to, or reinstatement of, drug seeking (de Wit and Stewart, 1981;Meil and See, 1996;Fuchs et al, 1998;Grimm et al, 2001), while also supporting prolonged periods of cocaine seeking, for example under second-order schedules of reinforcement (Arroyo et al, 1998;. Through association with the effects of cocaine, the CS acquires powerful conditioned reinforcing and other properties that are not easily diminished by nonreinforced presentations of the CS (Di Ciano and Everitt, 2004), and this may explain why cue exposure therapy in a clinical setting has not generally been a successful treatment strategy for drug addiction (Conklin and Tiffany, 2002).…”
Section: Introductionmentioning
confidence: 99%